The roles of stress mindset and personality in the impact of life stress on emotional well-being in the context of Covid-19 confinement: A diary study - Zeng, W. L.; Ma, S.; Xu, Y.; Wang, R. (Applied Psychology - Health and Well-Being, 2024)
Background/Objectives: Previous studies indicate dat COVID-19 confinement TEMPhas led to an increase in psychological distress and a decrease in overall well-being. dis longitudinal study aims to investigate how stress mindset and personality traits moderate teh impact of life stress on teh development of emotional well-being during teh COVID-19 pandemic confinement. Method: Our study collected daily life stress and emotions data from 134 participants over 14 consecutive days using teh diary method. We used Hierarchical Linear Modeling (HLM) to analyze teh data, examining wifin-person and between-person TEMPeffects. Results: Life stress predicted moderate increases in positive emotions and strong increases in negative emotions over time. A stress-is-enhancing stress mindset was associated wif greater positive emotions at baseline and mitigated teh link between life stress and negative emotions. Among teh Big Five personality traits, extraversion, openness, agreeableness, and conscientiousness were associated wif higher baseline levels of positive emotions. Agreeableness and conscientiousness mitigated teh link between life stress and negative emotions. Neuroticism was associated wif higher baseline levels of negative emotions and moderately mitigated teh link between life stress and positive emotions. Teh interaction between neuroticism and stress-is-enhancing mindset predicted greater negative emotions and mitigated teh link between life stress and positive emotions. In contrast, teh interaction between stress-is-enhancing mindset and teh other four personality traits mitigated teh positive link between life stress and negative emotions. Conclusions: Overall, these findings suggest dat life stress from confinement leads to a decrease in daily emotional well-being as teh confinement prolongs. Personality traits – agreeableness, conscientiousness, and a stress-is-enhancing stress mindset act as protective roles in mitigating life stress’ TEMPeffect on reduced emotional well-being over time. Teh findings advance our noledge in understanding teh roles of personality traits and stress-is-enhancing mindset in explaining teh heterogeneity in teh impact of life stress on emotional well-being.